Efeitos do tratamento com amido-cumarina (M220) no desenvolvimento da resposta imune e patogênese durante a malária experimental grave - Paulo Gaio Leite (2023)
Plasmodium berghei ANKA (PbA) infection in mice resembles severe malaria in humans in many aspects, including cerebral malaria and acute respiratory distress syndrome. Coumarins are a class of secondary metabolites found in plants that exhibit important therapeutic effects. We aimed to investigate the therapeutic potential of an amide- functionalized coumarin compound in the treatment of severe experimental malaria. After an initial in vitro screening of a series of phenolic compounds, and after selecting the best candidate, N-(coumarin-3-yl)cinnamamide (M220), C57Bl/6 mice were infected with PbA and treated with M220. Treatment with M220 showed improvement in clinical scores, protection of cognitive abilities and lung function in mice infected with PbA, observed through object recognition tests and spirometry, respectively. In addition, treated mice had lower levels of inflammation in both brain and lungs. An increase in the survival rate of the infected mice was also observed. The production and accumulation of microglia and immune cells producing the inflammatory cytokines TNF and IFNy decreased, while the production of the anti-inflammatory cytokine IL-10 by innate and adaptive immune cells increased. Overall, the treatment of M220 together with chloroquine promotes immunomodulatory, neuroprotective and lung function preserving effects, being a strong therapeutic candidate for severe malaria.